FORMATION OF FOREIGN LANGUAGE COMMUNICATIVE COMPETENCE OF STUDENTS OF NON-LINGUISTICS HIGHER EDUCATIONAL INSTITUTIONS BY THE METHOD OF INNOVATIVE DICTATIONS - Baranenkova, Natalia; Lashuk, Natalia (Educological discourse, 2019)
The article deals with the issue of the effectiveness of using dictogloss as a way of enhancing communicative speech activity, critical thinking and creative potential of students of non-language higher educational institutions in ESP classes. The key stages of the traditional dictogloss are considered: 1) preparation; 2) dictation; 3) reproduction; 4) analysis and reflection, comparing texts created by subgroups with the original or with texts of other subgroups. The main principles (such as the principle of cooperation training and the use of interactive technologies, the principle of the curriculum and the educational process connection, the principle of diversification, the principle of the development of mental, mnemic and perceptual processes, the principle of emotionality, the principle of systematicity and consistency) aimed at ensuring the outcomes and effectiveness of innovation dictations and the ways of their implementation are outlined. The main modified versions of the dictogloss are analyzed and recommendations for their preparation in ESP classes are provided: dictogloss-negotiations, «student-control» dictogloss, student-student mode, «Summary» dictogloss, «Express your own opinion», «Reodering dictogloss», «Add details», «Picture» dictogloss. Dictogloss is determined to be an effective activity for teaching ESP, since it can be applied to different levels of foreign language proficiency and adapted for any specialism. The advantages of the dictogloss are emphasized: it can be used to represent a new topic, to revise and practice vocabulary or grammar material; it does not require more time for preparation than other types of activity; the teacher can change the forms of dictations, adding a competitive element or element of the gamification; it can become a source of motivation for learning a foreign language and a way of diversifying pedagogical techniques and technologies.